Lithium cobalt oxide electrode material and preparation method thereof, electrode plate and preparation method thereof, lithium battery and electronic equipment

By forming an amorphous oxide coating on the lithium cobalt oxide electrode material, the problem of surface doping affects stability is solved, the conductivity and structural stability are improved, and the electrochemical performance is enhanced.

CN119118210AInactive Publication Date: 2024-12-13UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411058450.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium cobalt oxide surface coating combined with surface doping methods will affect the stability and safety of lithium cobalt oxide battery surface materials, resulting in a degradation of electrochemical performance.

Method used

The precursor is obtained by mixing the sodium, potassium, silicon, and M metal salt with a preset molar ratio. It is added to deionized water and stirred and mixed with lithium cobalt oxide powder. It is processed by high-pressure hydrothermal method and sintering and grinding to form amorphous oxidation. The doping process of the substance-cobalt lithium cobalt oxide electrode material is spontaneously carried out during the sintering process, forming a gradient diffusion amorphous oxide layer to improve conductivity and structural stability.

Benefits of technology

It improves the conductivity and capacity density of lithium cobalt oxide materials, suppresses harmful phase change under high voltage, reduces the interface charge transfer impedance, and enhances electrochemical stability and cycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118210A_ABST
    Figure CN119118210A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, in particular to a lithium cobalt oxide electrode material and a preparation method thereof, an electrode plate and a preparation method thereof, a lithium battery and electronic equipment. The preparation method comprises the following steps: mixing a sodium source, a potassium source, a silicon source, an aluminum source and M metal salt according to a preset molar ratio to obtain a precursor; adding the precursor into deionized water, and uniformly stirring to obtain a solution A; then adding lithium cobalt oxide powder into the solution A, and continuously stirring to obtain a mixed solution; after the reaction of the mixed solution is completed and the mixed solution is dried, a mixture is obtained, and after the mixture is sintered and ground, the required amorphous oxide coated lithium cobalt oxide electrode material is obtained. In the sintering process, the surface of the lithium cobalt oxide material is coated with the amorphous oxide layer, the lithium cobalt oxide material is coated with the amorphous oxide layer, and the structural stability of the lithium cobalt oxide material is improved; in the process, metal elements such as N , K, A < l > and M are correspondingly doped into ion sites of lithium cobalt oxide, so that the conductivity and the capacity density of the lithium cobalt oxide material are improved, and an ion framework of the lithium cobalt oxide material is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium cobalt oxide electrode material and a preparation method thereof, an electrode sheet and a preparation method thereof, a lithium battery, and an electronic device. [Background technology]

[0002] Lithium-ion batteries using layered lithium cobalt oxide (LCO) as electrode material have always dominated the battery market due to their high energy density, large compaction density, stable charge and discharge voltage, and high operating voltage. Today, LCO still has great potential to achieve higher specific capacity. Methods to increase energy density usually include: increasing compaction, adjusting the mass ratio of active materials, pre-lithiation, and increasing the cutoff voltage of lithium cobalt oxide. Among them, increasing the upper cutoff voltage of lithium cobalt oxide to extract more Li+ from LCO to increase capacity is very effective. However, charging LCO to a high voltage will bring about some degradation of material properties, resulting in capacity decay and poor cycle stability.

[0003] In order to improve the interface stability and maintain the electrochemical performance of LCO, various surface coating and doping strategies have been explored. Studies have shown that surface coating combined with surface doping is an effective way to alleviate interface problems under high voltage. However, many of the current surface coating combined with surface doping methods will affect the stability and safety of lithium cobalt oxide surface materials, thereby adversely affecting their electrochemical performance. [Summary of the invention]

[0004] In order to solve the problem that the existing method of lithium cobalt oxide surface coating combined with surface doping will affect the stability and safety of the surface material of lithium cobalt oxide batteries, the present invention provides a lithium cobalt oxide electrode material and a preparation method thereof, an electrode sheet and a preparation method thereof, a lithium battery, and an electronic device.

[0005] The present invention provides the following solutions to solve the above technical problems:

[0006] A preparation method of a lithium cobalt oxide electrode material comprises the following steps: mixing a sodium source, a potassium source, a silicon source, an aluminum source and an M metal salt according to a preset molar ratio to obtain a precursor, wherein the preset molar ratio is n(Na):n(K):n(A l):n(S i):n(M)=x:(1-x):0.2:3:0.8, 0<x<1; wherein the M metal element is Mg, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, I n, La, Ce; adding the precursor into deionized water and stirring evenly to obtain solution A; adding lithium cobalt oxide powder into solution A and continuing to stir to obtain a mixed solution; after the mixed solution is reacted and dried, a mixture is obtained, and the mixture is sintered and ground to obtain the desired amorphous oxide-coated lithium cobalt oxide electrode material; wherein the precursor forms an amorphous oxide during the sintering process; wherein the mass ratio of lithium cobalt oxide powder to amorphous oxide is 1: (0.1% to 10%).

[0007] Preferably, the sodium source includes one of sodium hydroxide, sodium nitrate, sodium sulfate, and sodium acetate; the potassium source includes one of potassium hydroxide, potassium nitrate, potassium sulfate, and sodium potassium acetate; the silicon source includes silicon tetrachloride; the aluminum source includes one of aluminum nitrate, aluminum sulfate, and aluminum acetate; and the M metal salt includes one of nitrate, sulfate, acetate, oxalate, and ammonium salt.

[0008] Preferably, the structural formula of the amorphous oxide is (NaxK1-x)(A l 0.2M0.8)S i 3O8, 0<x<1.

[0009] Preferably, fully reacting and drying the mixed solution specifically comprises the following steps: charging the mixed solution into a high-pressure hydrothermal autoclave for reaction, the reaction time is 8-24 hours, the reaction temperature is 160-280°C, after the reaction is completed, taking out the precipitate, washing and filtering with anhydrous ethanol, and drying to obtain the mixture.

[0010] Preferably, grinding and sintering the mixture specifically comprises the following steps: placing the mixture in a heating furnace for sintering in an air atmosphere, sintering at a temperature of 400-800°C for 2-6 hours, and obtaining the desired amorphous oxide-coated lithium cobalt oxide electrode material after natural cooling and grinding and sieving.

[0011] The present invention also provides a lithium cobalt oxide electrode material, which is prepared by the preparation method of the lithium cobalt oxide electrode material as described above, and comprises lithium cobalt oxide and an amorphous oxide coated on the surface of the lithium cobalt oxide, wherein the amorphous oxide is a mixture of a sodium source, a potassium source, a silicon source, an aluminum source and an M metal salt, and the molar ratio of the sodium source, the potassium source, the silicon source, the aluminum source and the M metal salt is n(Na):n(K):n(A l):n(S i):n(M)=x:(1-x):0.2:3:0.8, 0<x<1; wherein the M metal element is one or more of Mg, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, In, La, and Ce.

[0012] The present invention also provides an electrode sheet, comprising an electrode slurry and a current collector, wherein the electrode slurry comprises the lithium cobalt oxide electrode material as described above, and the electrode slurry is disposed on the current collector.

[0013] The present invention also provides a method for preparing an electrode sheet, which is used to prepare the electrode sheet as described above, comprising the following steps: mixing the lithium cobalt oxide electrode material, conductive graphite, PVDF binder, and N-methylpyrrolidone in a certain mass ratio to prepare an electrode slurry; forming the electrode slurry on a current collector and drying it to obtain the desired electrode sheet.

[0014] The present invention also provides a lithium battery, comprising a positive electrode part, an electrolyte and a negative electrode part; wherein the positive electrode part comprises the electrode sheet as described above.

[0015] The present invention further provides an electronic device, comprising a carrying device and the lithium battery as described above, wherein the lithium battery is arranged on the carrying device.

[0016] Compared with the prior art, the lithium cobalt oxide electrode material and preparation method thereof, electrode sheet and preparation method thereof, lithium battery and electronic equipment provided by the present invention have the following advantages:

[0017] 1. The preparation method of the lithium cobalt oxide electrode material provided by the present invention comprises mixing a sodium source, a potassium source, a silicon source, an aluminum source and an M metal salt according to a preset molar ratio to obtain a precursor, wherein the preset molar ratio is n(Na):n(K):n(A l):n(S i):n(M)=x:(1-x):0.2:3:0.8, 0<x<1; wherein the M metal element is Mg, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, I n, La, Ce; then adding the precursor into deionized water and stirring evenly to obtain solution A; then adding lithium cobalt oxide powder into solution A and continuing stirring to obtain a mixed solution; after the mixed solution is reacted and dried to obtain a mixture, the mixture is sintered and ground to obtain the desired amorphous oxide-coated lithium cobalt oxide electrode material; wherein the precursor forms an amorphous oxide during the sintering process; the mass ratio of lithium cobalt oxide powder to amorphous oxide is 1: (0.1% to 10%); during the sintering process, the surface of the lithium cobalt oxide material is coated with an amorphous oxide layer, during which Na and K alkali metal elements are doped into the Li ion site to improve the conductivity and capacity density of the lithium cobalt oxide material, A l, M and other metal elements doped with transition metal ions expand the ion framework of lithium cobalt oxide materials, making lithium ions easier to migrate. The doping process is a gradient diffusion that occurs spontaneously during the sintering process; the amorphous oxide layer has a good lithium ion transmission rate; the amorphous oxide layer coats the lithium cobalt oxide material, improves the structural stability of the lithium cobalt oxide material, inhibits the harmful phase change of the lithium cobalt oxide material under high voltage, reduces the grain boundary dislocation and internal stress in the high delithiation state, and then reduces the charge transfer impedance at the interface between lithium cobalt oxide and the electrolyte, which is beneficial to the electrochemical stability of lithium cobalt oxide materials for lithium-ion batteries.

[0018] 2. Sodium compounds include one of sodium hydroxide, sodium nitrate, sodium sulfate, and sodium acetate; potassium compounds include one of potassium hydroxide, potassium nitrate, potassium sulfate, and sodium potassium acetate; silicon compounds include but are not limited to silicon tetrachloride; aluminum compounds include one of aluminum nitrate, aluminum sulfate, and aluminum acetate; M metal salts include one of nitrates, sulfates, acetates, oxalates, and ammonium salts; according to different needs, suitable raw materials are selected to prepare the required lithium cobalt oxide positive electrode materials, so that lithium cobalt oxide positive electrode materials can be more widely used in lithium batteries.

[0019] 3.充分反应并干燥混合溶液具体包括以下步骤:将混合溶液装入高压水热釜中进行反应,反应时间为8 - 24小时,反应温度为160 - 280℃,反应结束后取出沉淀物,用无水乙醇清洗并抽滤,干燥后得到所述混合物;采用水热沉淀法在钴酸锂材料表面均匀生长出致密保护膜,与当前常用的球磨法、气相沉积法等方法相比,该方法简单,制备成本低。由于非晶材料体相杨氏模量低,

[0020] it has good conformability and can uniformly coat the surface of lithium cobaltate material.

[0021] 4.对混合物进行研磨烧结处理具体包括以下步骤:将混合物置于加热炉中在空气氛围下进行烧结,在400 - 800℃的温度下保温烧结2 - 6小时,待自然冷却并研磨过筛后得到所需的非晶氧化物包覆的钴酸锂电极材料;进行烧结处理后再进行研磨,可提高钴酸锂电极材料晶格结构的稳定性。

[0022] 5.非晶氧化物的结构式为(NaxK1 - x)(Al0.2M0.8)Si3O8,0 < x < 1;非晶氧化物层具有良好的锂离子传输速率;非晶氧化物层包覆钴酸锂材料,提高钴酸锂材料的结构稳定性,抑制高电压下钴酸锂材料的有害相变,降低高脱锂态晶界位错与内应力,进而降低钴酸锂与电解液界面的电荷转移阻抗,因此有利于锂离子电池钴酸锂材料的电化学稳定性。

[0023] 6.本发明提供一种钴酸锂电极材料,通过如上所述的钴酸锂电极材料的制备方法制备获得;上述钴酸锂电极材料的制备方法中已说明钴酸锂电极材料的有益效果,在此不再赘述。

[0024] 7.本发明还提供一种电极片,包括电极浆料和集流体,电极浆料包括如上所述的钴酸锂电极材料,电极浆料设置在集流体上;具有与上述钴酸锂电极材料相同的有益效果,在此不再赘述。

[0025] 8. The present invention also provides a method for preparing an electrode sheet, which is used to prepare the electrode sheet as described above, comprising the following steps: mixing lithium cobalt oxide electrode material, conductive graphite, PVDF binder, and N-methylpyrrolidone (NMP) in a certain mass ratio to prepare an electrode slurry; forming the electrode slurry on a current collector and drying it to obtain the desired electrode sheet; N-methylpyrrolidone (NMP) is a polar solvent with strong selectivity and good stability, and is an excellent solvent for lithium battery electrode slurry; PVDF binder does not react with electrode materials, has good solubility in solvents and has high adhesion.

[0026] 9. The present invention also provides a lithium battery, comprising a positive electrode part, an electrolyte and a negative electrode part; wherein the positive electrode part comprises the electrode sheet as described above; and has the same beneficial effects as the above-mentioned lithium cobalt oxide electrode material, which will not be repeated here.

[0027] 10. The present invention also provides an electronic device, comprising a carrier and the lithium battery as described above, wherein the lithium battery is arranged on the carrier; the electronic device has the same beneficial effects as the above-mentioned lithium cobalt oxide electrode material, which will not be described in detail here.

Brief Description of the Drawings

[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0029] Figure 1 It is a schematic flow chart of the steps of the method for preparing the lithium cobalt oxide electrode material provided by the first embodiment of the present invention.

[0030] Figure 2 1 is a schematic flow chart of specific steps of step S4 of the method for preparing a lithium cobalt oxide electrode material provided in the first embodiment of the present invention.

[0031] Figure 3 1 is a schematic diagram of a specific step flow chart of step S5 of the method for preparing a lithium cobalt oxide electrode material provided in the first embodiment of the present invention.

[0032] Figure 4 It is a cycle performance curve diagram of pure lithium cobalt oxide and the lithium cobalt oxide electrode material provided by the second embodiment of the present invention under different experimental conditions.

[0033] Figure 5 It is an SEM magnified image of the lithium cobalt oxide electrode material provided in the second embodiment of the present invention and the lithium cobalt oxide material provided in other comparative examples.

[0034] Figure 6It is an enlarged TEM image of the lithium cobalt oxide electrode material provided in the second embodiment of the present invention and the lithium cobalt oxide material provided in other comparative examples.

[0035] Figure 7 It is a schematic diagram of the structure of an electrode sheet provided in the third embodiment of the present invention.

[0036] Figure 8 It is a schematic flow chart of a method for preparing an electrode sheet provided in the fourth embodiment of the present invention.

[0037] Fig. 9 It is a schematic structural diagram of a lithium battery provided by the fifth embodiment of the present invention.

[0038] Fig.10 It is a structural schematic diagram of an electronic device provided by the sixth embodiment of the present invention.

[0039] Description of the accompanying drawings:

[0040] 70. lithium battery; 71. positive electrode; 72. negative electrode; 73. electrolyte;

[0041] 100. electrode sheet; 101. current collector; 102. electrode slurry; 103. lithium cobalt oxide electrode material; 200. electronic device; 201. carrier device. [Specific implementation method]

[0042] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and implementation examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0043] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only.

[0044] In the present invention, the directions or positional relationships indicated by the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "middle", "vertical", "horizontal", "lateral", "longitudinal" and the like are based on the directions or positional relationships shown in the drawings. These terms are mainly used to better describe the present invention and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific direction, or to be constructed and operated in a specific direction.

[0045] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those skilled in the art, the specific meanings of these terms in the present invention can be understood according to specific circumstances.

[0046] In addition, the terms "installed", "set", "provided with", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, elements, or components. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0047] See also Figure 1 The first embodiment of the present invention provides a method for preparing a lithium cobalt oxide electrode material, which comprises the following steps:

[0048] Step S1: mixing a sodium source, a potassium source, a silicon source, an aluminum source and an M metal salt according to a preset molar ratio to obtain a precursor;

[0049] Step S2: adding the precursor into deionized water and stirring evenly to obtain solution A;

[0050] Step S3: adding lithium cobalt oxide powder to solution A and continuing to stir to obtain a mixed solution;

[0051] Step S4: completing the reaction of the mixed solution and drying it to obtain a mixture;

[0052] Step S5: The mixture is sintered and ground to obtain the desired amorphous oxide-coated lithium cobalt oxide electrode material.

[0053] Specifically, during the sintering process, the surface of the lithium cobalt oxide material is coated with an amorphous oxide layer. During this process, alkali metal elements Na and K are doped into the Li ion site to improve the conductivity and capacity density of the lithium cobalt oxide material. Metal elements such as Al and M are doped into the transition metal ion site to expand the ion framework of the lithium cobalt oxide material, making it easier for lithium ions to migrate. The doping process is a gradient diffusion that occurs spontaneously during the sintering process. The amorphous oxide layer has a good lithium ion transmission rate. The amorphous oxide layer coats the lithium cobalt oxide material, improves the structural stability of the lithium cobalt oxide material, inhibits harmful phase changes of the lithium cobalt oxide material under high voltage, reduces grain boundary dislocations and internal stresses in a high-delithiation state, and thereby reduces the charge transfer impedance at the interface between the lithium cobalt oxide and the electrolyte, thereby being beneficial to the electrochemical stability of the lithium cobalt oxide material for lithium-ion batteries.

[0054] Specifically, the M metal element is one or more of Mg, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, In, La, and Ce.

[0055] Specifically, the M metal salt includes one of nitrate, sulfate, acetate, oxalate, and ammonium salt.

[0056] Specifically, the sodium source includes one of sodium hydroxide, sodium nitrate, sodium sulfate, and sodium acetate; the potassium source includes one of potassium hydroxide, potassium nitrate, potassium sulfate, and sodium potassium acetate; the silicon source includes one of silicon tetrachloride or other organic silicon sources; the aluminum source includes one of aluminum nitrate, aluminum sulfate, and aluminum acetate; according to different needs, suitable raw materials are selected to prepare the required lithium cobalt oxide positive electrode material, so that the lithium cobalt oxide positive electrode material can be more widely used in lithium batteries.

[0057] Specifically, the total metal ion concentration of the sodium source, potassium source, silicon source, aluminum source and M metal salt is 1 mol / L.

[0058] Furthermore, in some specific embodiments, the corresponding molar ratio of the precursors in step S1 is n(Na):n(K):n(A l):n(S i):n(M)=x:(1-x):0.2:3:0.8, 0<x<1.

[0059] Furthermore, during sintering the mixture in step S5 , the precursor forms an amorphous oxide.

[0060] Furthermore, the mass ratio of the lithium cobalt oxide powder to the amorphous oxide added in step S2 is 1:(0.1% to 10%).

[0061] Furthermore, the structural formula of the amorphous oxide is (NaxK1-x)(A l 0.2M0.8)S i 3O8, (x=0-1); the amorphous oxide layer has a good lithium ion transmission rate; the amorphous oxide layer coats the lithium cobalt oxide material, improves the structural stability of the lithium cobalt oxide material, inhibits the harmful phase change of the lithium cobalt oxide material under high voltage, reduces the grain boundary dislocation and internal stress in the high delithiation state, and thus reduces the charge transfer impedance at the interface between the lithium cobalt oxide and the electrolyte, which is beneficial to the electrochemical stability of the lithium cobalt oxide material of the lithium ion battery.

[0062] Specifically, in the above step S3, to ensure that the lithium cobalt oxide powder can be fully dissolved in solution A, the lithium cobalt oxide powder is added to solution A and stirred for 1-10 hours, at a stirring temperature of 30-50° C., and at a stirring speed of 300-1500 rpm.

[0063] For further information, please refer to Figure 2 , the above step S4 further includes the following steps:

[0064] S41: placing the mixed solution into a high pressure hydrothermal autoclave for reaction, the reaction time is 8-24 hours, and the reaction temperature is 160-280° C.;

[0065] S42: After the reaction is completed, the precipitate is taken out, washed with anhydrous ethanol, and filtered, and dried to obtain a mixture

[0066] It can be understood that the hydrothermal precipitation method is used to uniformly grow a dense protective film on the surface of the lithium cobalt oxide material. Compared with the currently commonly used methods such as ball milling and vapor deposition, the method is simple and has low preparation cost; since the amorphous material has a low bulk Young's modulus and good conformality, it can be uniformly coated on the surface of the lithium cobalt oxide material.

[0067] Please refer to Figure 3 In some specific implementations, the above step S5 further includes the following steps:

[0068] S51: placing the mixture in a heating furnace for sintering in an air atmosphere, sintering at a temperature of 400-800° C. for 2-6 hours, and obtaining a powder material after natural cooling;

[0069] S52: Grind and disperse using a mortar or ball mill, and then screen through a 200-300 mesh sieve to obtain the desired amorphous oxide-coated lithium cobalt oxide electrode material.

[0070] Specifically, in the above step S51, the mixture can be placed in a muffle furnace for sintering, and the working temperature of the muffle furnace is gradually increased from room temperature to 400-800°C at 3-10°C / min, and the temperature is maintained for 2-6 hours, and then naturally cooled to obtain a powder material.

[0071] It is understandable that grinding after sintering can improve the stability of the lattice structure of the lithium cobalt oxide electrode material.

[0072] In order to further illustrate the method for preparing the lithium cobalt oxide electrode material provided by the embodiment of the present invention and the remarkable effects achieved thereby, the following specific embodiments and comparative examples are provided for illustration.

[0073] Experimental group 1: Prepare a lithium cobalt oxide electrode material, the specific steps are as follows:

[0074] Step 1, design the amorphous oxide structure formula as (Na 0.5 K 0.5 )(A l 0.2 Mg 0.2 T i 0.2 Fe 0.2 Ni 0.2 )S i 3 O 8, lithium cobalt oxide and amorphous layer are weighed at a mass ratio of 1:0.03, and the weighed sodium nitrate, potassium nitrate, aluminum nitrate, magnesium nitrate, titanyl sulfate, iron nitrate, nickel nitrate, and silicon tetrachloride are added into deionized water, and stirred for 1 hour until the solution is clear to obtain solution A;

[0075] Step 2, adding the lithium cobalt oxide powder weighed according to the above mass ratio evenly to the stirring solution A, and continuing to stir until the mixture is uniform, the stirring time is 4 hours, and the stirring speed is 1000 rpm;

[0076] Step 3, adding the mixed solution into a high-pressure hydrothermal autoclave for reaction at a temperature of 180° C. for 16 hours. After the reaction is completed, the precipitate is taken out, washed, filtered, and dried to obtain a powder;

[0077] Step 4, placing the material obtained in step 3 in a heating furnace for sintering in an air atmosphere at a sintering temperature of 450° C. and a sintering time of 3 h, and obtaining a powder material after natural cooling;

[0078] Step 5, screening the lithium cobalt oxide material obtained in step 4 through a sieve to obtain the desired amorphous oxide-coated lithium cobalt oxide material.

[0079] Experimental group 2: The difference from experimental group 1 is that the reaction temperature in step 3 is changed to 220°C; the other experimental conditions are the same.

[0080] Experimental group 3: The difference from experimental group 1 is that the reaction time in step 3 is 10 h, and the other experimental conditions are the same.

[0081] Comparative Example 1: The difference from Experimental Group 1 is that the reaction temperature in step 3 is 150° C.; the other experimental conditions are the same.

[0082] Comparative Example 2: The difference from Experimental Group 1 is that the reaction time in step 3 is 6 h, and the other experimental conditions are the same.

[0083] Comparative Example 3: The difference from Experimental Group 1 is that the sintering temperature in step 4 is 900° C.; the other experimental conditions are the same.

[0084] Comparative Example 4: The difference from Experimental Group 1 is that the sintering time in step 4 is 8 h; the other experimental conditions are the same.

[0085] Table 1. Process parameters of each experimental group and comparative example

[0086] Sample name Covering ratio Water temperature Water heating time Sintering temperature Sintering time Experimental Group 1 3% 180℃ 16h 450℃ 3h Experimental Group 2 3% 220℃ 16h 450℃ 3h Experimental Group 3 3% 180℃ 10h 450℃ 3h Comparative Example 1 3% 150℃ 16h 450℃ 3h Comparative Example 2 3% 180℃ 6h 450℃ 3h Comparative Example 3 3% 180℃ 16h 900℃ 3h Comparative Example 4 3% 180℃ 16h 450℃ 8h

[0087] The electrochemical properties of the experimental groups 1-3, comparative examples 1-4 and the blank group (pure lithium cobalt oxide material) were tested: a half-cell was used to test the electrochemical properties of the prepared materials, and the lithium cobalt oxide electrode was prepared with the coated lithium cobalt oxide material. Then, the lithium cobalt oxide electrode, the electrolyte and the metal lithium disc were assembled into a button cell, and a cyclic charge and discharge test was performed between 3V and 4.55V. The activation was performed for 3 cycles, and the activation current density was 0.1C; the cycle was performed for 100 cycles, and the cyclic current density was 0.5C (1C=200mAh / g). The charge and discharge test results are shown in Table 2.

[0088] Table 2: Comparison of electrochemical performance results of each experimental group, comparative example and pure lithium cobalt oxide

[0089]

[0090] Combined with Table 2 and the accompanying drawings of the specification Figure 4 It can be seen that the electrochemical performance of lithium cobalt oxide material coated with amorphous oxide is more stable, with higher initial capacity and coulombic efficiency, and longer cycle performance.

[0091] Figure 5 (b) and Figure 5 (c) are SEM images of lithium cobalt oxide electrode materials prepared in Comparative Examples 1 and 2, respectively. It can be seen that a too low hydrothermal reaction temperature will lead to uneven growth of the coating layer on the particle surface, resulting in surface rupture, while an insufficient hydrothermal reaction time will result in loose growth of the coating material and the particle surface.

[0092] Figure 6 (b) and Figure 6 (c) are TEM images of lithium cobalt oxide electrode materials prepared in Comparative Examples 3 and 4, respectively. It can be seen that too high a sintering temperature and too long a sintering time will cause the surface-coated amorphous material to be partially or completely converted into a single crystal material, thereby affecting the stability and electrochemical properties of the lithium cobalt oxide material.

[0093] A second embodiment of the present invention provides a lithium cobalt oxide electrode material, which is prepared by the preparation method of the lithium cobalt oxide electrode material as described above, and includes lithium cobalt oxide and an amorphous oxide coated on the surface of the lithium cobalt oxide, wherein the amorphous oxide is a mixture of a sodium source, a potassium source, a silicon source, an aluminum source and an M metal salt, and the molar ratio of the sodium source, the potassium source, the silicon source, the aluminum source and the M metal salt is n(Na):n(K):n(A l):n(Si):n(M)=x:(1-x):0.2:3:0.8, 0<x<1; wherein the M metal element is one or more of Mg, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, In, La, and Ce; the beneficial effects of the lithium cobalt oxide electrode material have been described in the preparation method of the lithium cobalt oxide electrode material, which will not be repeated here.

[0094] For details, please refer to Figure 5 (a) and Figure 6 (a) It can be seen that the particle surface coating layer (i.e., the amorphous oxide layer) of the lithium cobalt oxide electrode material provided in the second embodiment obtained by the preparation method of the lithium cobalt oxide electrode material provided in the first embodiment grows uniformly and tightly; and the amorphous layer on the surface does not obviously transform into a single crystal material; thereby improving the stability and electrochemical properties of the lithium cobalt oxide material.

[0095] Please refer to Figure 7 The third embodiment of the present invention provides an electrode sheet 100, including an electrode slurry 102 and a current collector 101, the electrode slurry 102 includes the lithium cobalt oxide electrode material 103 provided in the second embodiment of the present invention, and the electrode slurry 102 is arranged on the current collector 103; it has the same beneficial effects as the above-mentioned lithium cobalt oxide electrode material, which will not be repeated here.

[0096] Please refer to Figure 8 The fourth embodiment of the present invention provides a method for preparing an electrode sheet, which is used to prepare the electrode sheet provided by the third embodiment of the present invention, comprising the following steps:

[0097] S60: mixing the lithium cobalt oxide electrode material, conductive graphite, PVDF binder, and N-methylpyrrolidone (NMP) in a certain mass ratio to prepare an electrode slurry;

[0098] S61: forming the positive electrode slurry on the current collector and placing it in a vacuum box for drying;

[0099] S62: After drying, the current collector is pressed and cut to obtain the required electrode sheet.

[0100] Specifically, the above-mentioned certain mass ratio is 1:(7-18):(1-2):1.

[0101] It can be understood that in step S60, N-methylpyrrolidone (NMP) is a polar solvent with strong selectivity and good stability, and is an excellent solvent for lithium battery electrode slurry. The PVDF binder does not react with the electrode material, has good solubility in the solvent and has high adhesion.

[0102] Specifically, step S61 further includes the following steps:

[0103] S610: baking the current collector coated with the electrode slurry at 80° C. for 6-12 hours to remove the NMP solvent;

[0104] S611: The electrode sheet obtained in step S610 is placed in a vacuum oven and baked at 80° C. for 6-12 hours to remove moisture adsorbed in the electrode sheet.

[0105] Specifically, in step S61, the electrode slurry is preferably coated on the copper foil by wet coating, with a coating thickness of 50-150 microns.

[0106] Please refer to Fig. 9 The fifth embodiment of the present invention provides a lithium battery 70, including a positive electrode part 71, an electrolyte 73 and a negative electrode part 72; wherein the positive electrode part 71 includes an electrode sheet formed by the lithium cobalt oxide electrode material provided in the second embodiment of the present invention; and has the same beneficial effects as the above-mentioned lithium cobalt oxide electrode material, which will not be repeated here.

[0107] Optionally, the material of the negative electrode structure 72 may include but is not limited to any one or a combination of stainless steel, copper, nickel, aluminum, gold, silver, chromium, platinum, titanium and the like; in this embodiment, the negative electrode structure 72 may also include metallic lithium, graphite, lithium titanate, silicon negative electrode alloy and the like.

[0108] The electrolyte 73 may include but is not limited to: LiPF 6 、L i C l O 4 、L i BF 4 , Li BOB, Li TFS I, Li AsF 6 A mixed solvent of ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC).

[0109] Please refer to Fig.10 The sixth embodiment of the present invention provides an electronic device 200, including a carrier 201 and a lithium battery 50 provided in the fifth embodiment of the present invention, wherein the lithium battery 70 is disposed on the carrier 201. The electronic device 200 has the technical effects of high safety and good material recycling performance. It can be understood that the electronic device may include, for example, an electric vehicle, a mobile device, a smart home device, etc.

[0110] In various embodiments of the present invention, it should be understood that the size of the serial numbers of the above-mentioned processes does not mean the necessary order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.

[0111] Compared with the prior art, the lithium cobalt oxide electrode material and preparation method thereof, electrode sheet and preparation method thereof, lithium battery and electronic equipment of the present invention have the following advantages:

[0112] 1. The preparation method of the lithium cobalt oxide electrode material provided by the present invention comprises mixing a sodium source, a potassium source, a silicon source, an aluminum source and an M metal salt according to a preset molar ratio to obtain a precursor, wherein the preset molar ratio is n(Na):n(K):n(Al):n(Si):n(M)=x:(1-x):0.2:3:0.8, 0<x<1; wherein the M metal element is Mg, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, I n, La, Ce; then adding the precursor into deionized water and stirring evenly to obtain solution A; then adding lithium cobalt oxide powder into solution A and continuing stirring to obtain a mixed solution; after the mixed solution is reacted and dried to obtain a mixture, the mixture is sintered and ground to obtain the desired amorphous oxide-coated lithium cobalt oxide electrode material; wherein the precursor forms an amorphous oxide during the sintering process; the mass ratio of lithium cobalt oxide powder to amorphous oxide is 1: (0.1% to 10%); during the sintering process, the surface of the lithium cobalt oxide material is coated with an amorphous oxide layer, during which Na and K alkali metal elements are doped into the Li ion site to improve the conductivity and capacity density of the lithium cobalt oxide material, A l, M and other metal elements doped with transition metal ions expand the ion framework of lithium cobalt oxide materials, making lithium ions easier to migrate. The doping process is a gradient diffusion that occurs spontaneously during the sintering process; the amorphous oxide layer has a good lithium ion transmission rate; the amorphous oxide layer coats the lithium cobalt oxide material, improves the structural stability of the lithium cobalt oxide material, inhibits the harmful phase change of the lithium cobalt oxide material under high voltage, reduces the grain boundary dislocation and internal stress in the high delithiation state, and then reduces the charge transfer impedance at the interface between lithium cobalt oxide and the electrolyte, which is beneficial to the electrochemical stability of lithium cobalt oxide materials for lithium-ion batteries.

[0113] 2. Sodium compounds include one of sodium hydroxide, sodium nitrate, sodium sulfate, and sodium acetate; potassium compounds include one of potassium hydroxide, potassium nitrate, potassium sulfate, and sodium potassium acetate; silicon compounds include but are not limited to silicon tetrachloride; aluminum compounds include one of aluminum nitrate, aluminum sulfate, and aluminum acetate; M metal salts include one of nitrates, sulfates, acetates, oxalates, and ammonium salts; according to different needs, suitable raw materials are selected to prepare the required lithium cobalt oxide positive electrode materials, so that lithium cobalt oxide positive electrode materials can be more widely used in lithium batteries.

[0114] 3. The full reaction and drying of the mixed solution specifically include the following steps: The mixed solution is loaded into a high-pressure hydrothermal autoclave for reaction. The reaction time is 8 - 24 hours, and the reaction temperature is 160 - 280 °C. After the reaction, the precipitate is taken out, washed with anhydrous ethanol, filtered by suction, and dried to obtain the mixture; The hydrothermal precipitation method is used to uniformly grow a dense protective film on the surface of the lithium cobalt oxide material. Compared with the currently commonly used methods such as ball milling method and chemical vapor deposition method, the method is simple and the preparation cost is low. Since the amorphous material has a low bulk Young's modulus and good conformability, it can uniformly coat the surface of the lithium cobalt oxide material.

[0115] 4. The grinding and sintering treatment of the mixture specifically include the following steps: The mixture is placed in a heating furnace and sintered in an air atmosphere. It is kept warm and sintered at a temperature of 400 - 800 °C for 2 - 6 h. After natural cooling and grinding and sieving, the required lithium cobalt oxide electrode material coated with amorphous oxide is obtained; Grinding after the sintering treatment can improve the stability of the lattice structure of the lithium cobalt oxide electrode material.

[0116] 5. The structural formula of the amorphous oxide is (NaxK1-x)(Al0.2M0.8)Si3O8, where 0 < x < 1; The amorphous oxide layer has a good lithium ion transmission rate; The amorphous oxide layer coats the lithium cobalt oxide material, improves the structural stability of the lithium cobalt oxide material, inhibits the harmful phase transformation of the lithium cobalt oxide material under high voltage, reduces the grain boundary dislocations and internal stresses in the highly delithiated state, and thus reduces the charge transfer impedance at the interface between the lithium cobalt oxide and the electrolyte. Therefore, it is beneficial to the electrochemical stability of the lithium cobalt oxide material for lithium ion batteries.

[0117] 6. The present invention provides a lithium cobalt oxide electrode material, which is prepared by the preparation method of the lithium cobalt oxide electrode material as described above; The beneficial effects of the lithium cobalt oxide electrode material have been described in the above preparation method of the lithium cobalt oxide electrode material, and will not be elaborated here.

[0118] 7. The present invention also provides an electrode sheet, which includes electrode paste and a current collector. The electrode paste includes the lithium cobalt oxide electrode material as described above, and the electrode paste is disposed on the current collector; It has the same beneficial effects as the above lithium cobalt oxide electrode material, and will not be elaborated here.

[0119] 8. The present invention also provides a preparation method of an electrode sheet for preparing the electrode sheet as described above, including the following steps: The lithium cobalt oxide electrode material, conductive graphite, PVDF binder, and N-methylpyrrolidone (NMP) are mixed in a certain mass ratio to make electrode paste; The electrode paste is formed on the current collector and dried to obtain the required electrode sheet; N-methylpyrrolidone (NMP) is a polar solvent with strong selectivity and good stability, and is an excellent solvent for lithium battery electrode paste. The PVDF binder does not react with the electrode material, has good solubility in the solvent, and has high adhesiveness.

[0120] 9. The present invention also provides a lithium battery, comprising a positive electrode part, an electrolyte and a negative electrode part; wherein the positive electrode part comprises the electrode sheet as described above; and has the same beneficial effects as the above-mentioned lithium cobalt oxide electrode material, which will not be repeated here.

[0121] 10. The present invention also provides an electronic device, comprising a carrier and the lithium battery as described above, wherein the lithium battery is arranged on the carrier; the electronic device has the same beneficial effects as the above-mentioned lithium cobalt oxide electrode material, which will not be described in detail here.

[0122] The above is a detailed introduction to a lithium cobalt oxide electrode material and a preparation method thereof, an electrode sheet and a preparation method thereof, a lithium battery, and an electronic device disclosed in an embodiment of the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea; at the same time, for a person skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention, and any modifications, equivalent substitutions and improvements made within the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a lithium cobalt oxide electrode material, characterized in that: A sodium source, a potassium source, a silicon source, an aluminum source and a metal salt M are mixed according to a preset molar ratio to obtain a precursor, wherein the preset molar ratio is n(Na):n(K):n(Al):n(Si):n(M)=x:(1-x):0.2:3:0.8, 0<x<1; Wherein M metal element is one or more of Mg, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, In, La, Ce; The precursor was added into deionized water and stirred evenly to obtain solution A; Adding lithium cobalt oxide powder to solution A and continuing to stir to obtain a mixed solution; After the mixed solution is reacted and dried, a mixture is obtained; The mixture is sintered and ground to obtain the desired amorphous oxide-coated lithium cobalt oxide electrode material; wherein the precursor forms an amorphous oxide during the sintering process; The mass ratio of lithium cobalt oxide powder to amorphous oxide is 1: (0.1% to 10%).

2. The method for preparing the lithium cobalt oxide electrode material according to claim 1, characterized in that: The sodium source includes one of sodium hydroxide, sodium nitrate, sodium sulfate, and sodium acetate; the potassium source includes one of potassium hydroxide, potassium nitrate, potassium sulfate, and sodium potassium acetate; the silicon source includes silicon tetrachloride; the aluminum source includes one of aluminum nitrate, aluminum sulfate, and aluminum acetate; and the M metal salt includes one of nitrate, sulfate, acetate, oxalate, and ammonium salt.

3. The method for preparing the lithium cobalt oxide electrode material according to claim 1, characterized in that: The structural formula of the amorphous oxide is (Na x K1-x)(Al 0.2 M 0.8 )Si3O8,0<x<1.

4. The method for preparing a lithium cobalt oxide electrode material according to claim 1, characterized in that: The mixed solution is reacted and dried, and specifically comprises the following steps: The mixed solution is placed in a high-pressure hydrothermal autoclave for reaction, the reaction time is 8-24 hours, and the reaction temperature is 160-280° C. After the reaction is completed, the precipitate is taken out, washed and filtered with anhydrous ethanol, and dried to obtain the mixture.

5. The method for preparing the lithium cobalt oxide electrode material according to claim 1, characterized in that: The grinding and sintering process of the mixture specifically comprises the following steps: The mixture is placed in a heating furnace for sintering in an air atmosphere, and a powder material is obtained after sintering at a temperature of 400-800° C. for 2-6 hours; and the desired amorphous oxide-coated lithium cobalt oxide electrode material is obtained after natural cooling and grinding and sieving.

6. A lithium cobalt oxide electrode material, prepared by the method for preparing a lithium cobalt oxide electrode material according to any one of claims 1 to 5, characterized in that: The invention comprises lithium cobalt oxide and an amorphous oxide coated on the surface of the lithium cobalt oxide, wherein the amorphous oxide is a mixture of a sodium source, a potassium source, a silicon source, an aluminum source and an M metal salt, and the molar ratio of the sodium source, the potassium source, the silicon source, the aluminum source and the M metal salt is n(Na):n(K):n(Al):n(Si):n(M)=x:(1-x):0.2:3:0.8, 0<x<1; The M metal element is one or more of Mg, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, In, La, and Ce.

7. An electrode sheet, characterized in that: The invention comprises an electrode slurry and a current collector, wherein the electrode slurry comprises the lithium cobalt oxide electrode material as claimed in claim 6, and the electrode slurry is arranged on the current collector.

8. A method for preparing an electrode sheet, used for preparing the electrode sheet according to claim 7, characterized in that: The steps include: The lithium cobalt oxide electrode material, conductive graphite, PVDF binder and N-methylpyrrolidone are mixed in a certain mass ratio to prepare an electrode slurry; the electrode slurry is formed on a current collector and dried to obtain a desired electrode sheet.

9. A lithium battery, characterized in that: It comprises a positive electrode part, an electrolyte and a negative electrode part; wherein the positive electrode part comprises the electrode sheet as described in claim 7.

10. An electronic device, characterized in that: It comprises a carrying device and the lithium battery as claimed in claim 9, wherein the lithium battery is arranged on the carrying device.

Citation Information

Cited By

  • Aluminosilicate additive and synthesis method thereof, lithium battery and electronic equipment

    CN121317795A